French translation, cultural adaptation and validation of the BDDQ-AS for rhinoplasty patients - Daniel Milad; Marie-Renée Atallah; Youcef-Hamza Benamer; Mikhail Saltychev; Sam P. Most; Sami P. Moubayed (BMC, 2022)
The Body Dysmorphic Disorder Questionnaire-Aesthetic Surgery (BDDQ-AS) is a validated questionnaire that is used as a screening tool for body dysmorphic disorder (BDD) in aesthetic rhinoplasty patients. The BDDQ-AS questionnaire was translated from English to French according to international guidelines. Ten French-speaking rhinoplasty patients were interviewed in order to evaluate the understandability and acceptability of the translation and produce a final version. It was then administered to 165 consecutive patients. Psychometric properties were evaluated using item-reponse theory (IRT). Internal consistency was high, with Cronbach's alpha of 0.90 (95% lower CL 0.88). While the discrimination abilities of all the items were good (over 2.0), their difficulty parameters were shifted towards greater severity of symptoms. That shift could also be observed in information function graph for the entire scale. In other words, the BDDQ-AS performed better in patients with more severe body dysmorphic symptoms. In conclusion, the BDDQ-AS was translated, adapted, and psychometrically validated for use in a French-speaking population.